Parents' experiences of caring for their child in a Paediatric Intensive Care Unit: a literature review - Wan Mohd Annuar, W Solihatul Hafidzah; Lee, Siew Pien; Makhtar, Aniawanis (Elsevier Espana, S.L.U., 2021)
The objective is to identify the available literature on parents’ experiences in caring for children in the Paediatric Intensive Care Unit (PICU). Original research on parents experience in caring their child in PICU were identified from five online databases, namely CINAHL, Science Direct, Proquest, Cochrane, and Pubmed (2008–2018) using the terms “parent,” “experience,” “children”, “paediatric intensive care” and “caring.” We included articles addressing the parent's experiences while their child was admitted to PICU their needs and participation in the care of the child. Twenty-two papers have met the criteria for inclusion. Further review of these articles resulted in summarised topics – PICU parents’ experience, parental stressors, and parental needs. Current research demonstrates a diversity of parent's experiences while caring for their child; however, little is known about interventions to improve and support parents who are in a difficult situation when their child being treated in PICU.